La dynamique du terrorisme : Le cas des Brigades rouges - Legault, Albert (Études internationales, 1983)
The dynamics of terrorism seem to follow a double track evolution. On the one hand, terrorism presents at the beginning a strong ideological component, particularly in the case of left-wings oriented terrorism. As events unfurl, terrorism drifts further apart from its original objectives. In the final stage, the ideological component relate almost exclusively to the ideology of violence for its own sake. On the other hand, the state ideological commitment to the preservation of the state creates a process whereby terrorism movements are being increasingly « marginalized ». The state administrative legal and political functions bring about a process through which terrorists, henceforth, are perceived as criminals. The case of the Red Brigades in Italy is used to illustrate this double track process.